2015
DOI: 10.1039/c4lc01254b
|View full text |Cite
|
Sign up to set email alerts
|

High process yield rates of thermoplastic nanofluidic devices using a hybrid thermal assembly technique

Abstract: Over the past decade, thermoplastics have been used as alternative substrates to glass and Si for microfluidic devices because of the diverse and robust fabrication protocols available for thermoplastics that can generate high production rates of the desired structures at low cost and with high replication fidelity, the extensive array of physiochemical properties they possess, and the simple surface activation strategies that can be employed to tune their surface chemistry appropriate for the intended applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 47 publications
(96 reference statements)
0
48
0
Order By: Relevance
“…This value was less than 60 m C/m 2 reported by Stein et al 109 and 214 m C/m 2 reported by Schoch et al 107 for glass-based nanoslits measured at pH 8. However, surface charge measurements performed in a nanoslit hybrid device – PMMA substrate bonded to oxygen plasma treated COC cover plate –|σ s | was 57.3 mC/m 2 85 . The difference in surface charge density was attributed to more carboxyl groups generated on COC compared to PMMA when treated under similar oxygen plasma conditions.…”
Section: Relevant Electrokinetic Parameters For Nanoscale Electrical mentioning
confidence: 96%
See 3 more Smart Citations
“…This value was less than 60 m C/m 2 reported by Stein et al 109 and 214 m C/m 2 reported by Schoch et al 107 for glass-based nanoslits measured at pH 8. However, surface charge measurements performed in a nanoslit hybrid device – PMMA substrate bonded to oxygen plasma treated COC cover plate –|σ s | was 57.3 mC/m 2 85 . The difference in surface charge density was attributed to more carboxyl groups generated on COC compared to PMMA when treated under similar oxygen plasma conditions.…”
Section: Relevant Electrokinetic Parameters For Nanoscale Electrical mentioning
confidence: 96%
“…Furthermore, copolymers can be used as substrates for nanofluidic devices that have a range of physiochemical properties arising from differences in the ratio of monomeric components used in them. 85 …”
Section: Fabrication Of Nanofluidic Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…High-strength bonding is achievable by these processes at temperatures sufficiently low to minimise temperature-induced channel deformation. Nevertheless, polymer surface dissolution and softening may also lead to dimensional change or distortion (Uba et al 2015).…”
Section: Introductionmentioning
confidence: 99%